Understanding weed biology and herbicide resistance to improve weed management - Soni-Castillo, Neeta, author; Gaines, Todd A., advisor; Dayan, Franck E., committee member; Argueso, Cristiana T., committee member; Haley, Scott D., committee member (Colorado State University. Libraries, 2020)
Weed management is essential in agriculture, natural areas, and rangelands. Weed control has mainly relied on herbicides. These chemical compounds are a low-cost option, easy to apply, and very efficient to eliminate weeds. However, as part of survival strategies weed species have evolved mechanisms to overcome herbicides and continue their life cycle. Thus, it is imperative that we increase our knowledge in weed biology and resistance mechanisms to develop better management strategies. Here I present three chapters that cover these areas of study. First, as an intent to promote more tools for management strategies in winter wheat, a field survey was conducted to identify the potential to implement harvest weed seed control for problematic winter annual grasses in this cropping system. The second chapter covers the results of a herbicide resistance survey to screen for imazamox and quizalofop resistance of troublesome winter annual grasses in winter wheat and rangeland areas. The third chapter aimed to determine the distribution of native and introduced Phragmites australis haplotypes which is a riparian species problematic in rangeland and natural areas. Harvest weed seed control methods showed potential to manage downy brome, feral rye, and jointed goatgrass. Seed retention of these winter annual grasses was over 75% indicating that the majority of seeds could be collected during wheat harvest. After screening over 280 samples of winter annual grasses, only two feral rye populations showed resistance to imazamox. Further studies on resistance mechanisms showed that one population (A) can rapidly metabolize the herbicide compared to a susceptible and the second population (B) contained a target site mutation in the imazamox target enzyme. Introduced Phragmites australis haplotypes were identified in Colorado using molecular markers. In addition, a low-cost and quick genotyping tool was developed to encourage land managers to conduct more frequent monitoring. Main results from this dissertation are expected to contribute with the big endeavor of promoting integrated weed management solutions and better weed biology understanding.